2013
DOI: 10.1093/aepp/ppt033
|View full text |Cite
|
Sign up to set email alerts
|

Vouchers versus Lotteries: What Works Best in Promoting Chlamydia Screening? A Cluster Randomized Controlled Trial

Abstract: In this cluster randomised trial (N=1060), we tested the impact of financial incentives (£5 voucher vs. £200 lottery) framed as a gain or loss to promote Chlamydia screening in students aged 18-24 years, mimicking the standard outreach approach to student in halls of residence. Compared to the control group (1.5%), the lottery increased screening to 2.8% and the voucher increased screening to 22.8%. Incentives framed as gains were marginally more effective (10.5%) that loss-framed incentives (7.1%). This work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 72 publications
(102 reference statements)
4
22
0
Order By: Relevance
“…Moreover, the effect of providing fixed compensation was also significantly higher than the effect of the lotterybased rewards. This noteworthy result is partially at odds with some of the theoretical rationale for using lottery-based rewards, but it is also consistent with findings from another recent study conducted in the United Kingdom that made a similar comparison of lotteries to vouchers, in this case to promote chlamydia screening among 18-to 24-yearold students (Niza et al 2014). The findings from that study also indicated that fixed vouchers (worth ₤5) were significantly more effective in increasing screening than lotterybased rewards.…”
Section: Discussion Of Resultssupporting
confidence: 83%
“…Moreover, the effect of providing fixed compensation was also significantly higher than the effect of the lotterybased rewards. This noteworthy result is partially at odds with some of the theoretical rationale for using lottery-based rewards, but it is also consistent with findings from another recent study conducted in the United Kingdom that made a similar comparison of lotteries to vouchers, in this case to promote chlamydia screening among 18-to 24-yearold students (Niza et al 2014). The findings from that study also indicated that fixed vouchers (worth ₤5) were significantly more effective in increasing screening than lotterybased rewards.…”
Section: Discussion Of Resultssupporting
confidence: 83%
“…First, starting bids were not randomized due to the survey’s administration as a paper survey. Different WTA estimates may have been obtained if starting values had been randomized [ 79 , 80 ] or if the incentive structure had involved either losses or lotteries [ 81 ]. Second, the contingent valuation questions were part of a broader study, and we did not power the data collection specifically for the analyses described in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…It may be hard to generalise the findings from this study to screening studies more widely, due to existing differences in findings even within the same screening behaviour, 32,33 which may depend on the country and health-care context, the population being studied and details of the incentive scheme.…”
Section: Generalisability Of Findingsmentioning
confidence: 97%
“…[28][29][30] Other studies described incentive programmes, but did not provide a test of the impact of the incentive. 26,31 Of the relevant articles, four considered screening for chlamydia, 25,[32][33][34] three investigated breast or cervical screening, [35][36][37] five investigated tuberculosis (TB) screening or returning to collect test results, [38][39][40][41][42] two investigated work wellness programmes or private health-care plans providing preventative health-care screening, 27,43 and single papers describing incentives in diabetic retinopathy screening, 44 and glycated haemoglobin (HbA 1c ) plus cholesterol screening in patients with diabetes. 45 Three of the four studies investigating chlamydia screening observed a positive impact of incentives, 25,32,34 with evidence that vouchers were more effective than prize draws.…”
Section: Systematic Review Of Literature On Incentives In Screeningmentioning
confidence: 99%
See 1 more Smart Citation